The Legendary Saga as a Medium of Cultural Memory: A Study of Late Medieval Icelandic Manuscripts - Valpola-Walker, Alisa (Memory and the Medieval North, 2025)
This book examines how the legendary Scandinavian past is ‘remembered’ in two late medieval Icelandic saga manuscripts. Drawing on insights from cultural memory studies and material philology, it situates them in their literary, media, and historical contexts to argue that they served particular functions at their time of writing and then continued to shape cultural memories as they were read (or vocalised) in the centuries that followed.